Unconfined Groundwater Quality based on the Settlement Unit in Surakarta City - Munawar Cholil (Forum Geografi, 1997)
The quality of groundwater of unonfined aquifer with growing population density is endangered by population. This may cause serious problem as greatest portion of the population utility groundwater of unconfined aquifer as their drinking water. This research is aim at studying the difference in quality of groundwater of unonfined aquifer in Surakarta Munipicality by settlement units, and studying the impact settlement factors and groundwater depth on the quality of groundwater of unonfined aquifer. The research was executed by a survey methhod, taking 44 units of groundwater of unonfined aquifer samples at stratified proportional random from 44 villages. The samples were analyzed at the laboratory of Local Drinking Water Company (PDAM) of Surakarta. Data were analyzed using by stiff diagram, variance analysis, and multiple regression. The research reveals that there is very little differences in the quality of free groundwater in Surakarta, as it is shown by same chemical properties. Several chemical properties were found very high in concentration, but the rest were simultaniously low. On the basis of minimum quality of drinking water coli content have exeeded the allowed limit for drinking water.Among the settlement units observed, there were no significant differences in the physical, chemical (except pH), bacteriological factors. This means that differences among various depth of water. Electrical onductivity (EC), Na, Mg, H2CO3, H2SO4, and NH3 were found different among various depth of water table. Major chemical conentration were significant with geology formation. Population density, built up areas, size of settlement, building density, and the condition of drainage simultaniously affect the quality of free ground water. No differences among settlement units was observed the most important fators determining the free groundwater quality was population density.